Genome-wide association analysis on pre-harvest sprouting resistance and grain color in US winter wheat - Lin, Meng; Zhang, Dadong; Liu, Shubing; Zhang, Guorong; Yu, Jianming; Fritz, Allan K.; Bai, Guihua H. (My University, 2016)
Background: Pre-harvest sprouting (PHS) in wheat can cause substantial reduction in grain yield and end-use quality. Grain color (GC) together with other components affect PHS resistance. Several quantitative trait loci (QTL) have been reported for PHS resistance, and two of them on chromosome 3AS (TaPHS1) and 4A have been cloned. Methods: To determine genetic architecture of PHS and GC and genetic relationships of the two traits, a genome-wide association study (GWAS) was conducted by evaluating a panel of 185 U.S. elite breeding lines and cultivars for sprouting rates of wheat spikes and GC in both greenhouse and field experiments. The panel was genotyped using the wheat 9K and 90K single nucleotide polymorphism (SNP) arrays. Results: Four QTL for GC on four chromosomes and 12 QTL for PHS resistance on 10 chromosomes were identified in at least two experiments. QTL for PHS resistance showed varied effects under different environments, and those on chromosomes 3AS, 3AL, 3B, 4AL and 7A were the more frequently identified QTL. The common QTL for GC and PHS resistance were identified on the long arms of the chromosome 3A and 3D. Conclusions: Wheat grain color is regulated by the three known genes on group 3 chromosomes and additional genes from other chromosomes. These grain color genes showed significant effects on PHS resistance in some environments. However, several other QTL that did not affect grain color also played a significant role on PHS resistance. Therefore, it is possible to breed PHS-resistant white wheat by pyramiding these non-color related QTL.
Citation: Lin, M., Zhang, D. D., Liu, S. B., Zhang, G. R., Yu, J. M., Fritz, A. K., & Bai, G. H. (2016). Genome-wide association analysis on pre-harvest sprouting resistance and grain color in US winter wheat. Bmc Genomics, 17, 16. doi:10.1186/s12864-016-3148-6
Keywords: Triticum Aestivum; Pre-Harvest Sprouting Resistance; Grain Color; Genome- Wide Association Studies; Quantitative Trait Loci; Triticum-Aestivum L.